Additives Effects on Crystal Morphology of Dihydroxylammonium 5, 5ʹ-Bistetrazole-1, 1ʹ-diolate by Molecular Dynamics Simulations. Issue 4 (1st October 2016) - Xiong, Shu-Ling; Chen, Shu-Sen; Jin, Shao-Hua; Li, Li-Jie
Abstract : Dihydroxylammonium 5, 5′-bistetrazole-1, 1′-diolate (TKX-50) is a newly synthesized explosive with excellent comprehensive properties: high energy storage, low impact sensitivity, and low toxicity. To understand and improve the crystal morphology of TKX-50, we reported the polymer consistent force field to simulate the crystal morphology of TKX-50 by growth morphology (GM) method. We then used this force field in molecular dynamics (MD) simulations to predict the influences of additives on crystal facets of TKX-50. The calculated results indicate that ethanol, ethylene glycol, and acetic acid are more favorable to the spheroidization of TKX-50, which provides a theoretical support for the additive selection of crystalline system. Furthermore, we added the selected additives in the recrystallization system of TKX-50. The recrystallized samples possessed a small aspect ratio and were close to spherical in shape, which indicates that the experimental results are consistent with the simulated results.